2014
DOI: 10.1002/cbdv.201300161
|View full text |Cite
|
Sign up to set email alerts
|

Volatile‐Oils Composition, and Bioactivity of the Essential Oils of Plectranthus barbatus, P. neochilus, and P. ornatus Grown in Portugal

Abstract: Volatile-oils chemical composition and bioactivity of the essentail oils from Plectranthus barbatus, P. neochilus, and P. ornatus (Lamiaceae) were assessed. Aerial parts from these three related Plectranthus species were collected from cultivated plants grown in Portugal, during vegetative and flowering phases. Volatiles, isolated by distillation-extraction, were analyzed by GC and GC/MS. Monoterpene hydrocarbons (12-74%) and sesquiterpene hydrocarbons (4-45%) constituted the main fractions in all volatiles. α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 40 publications
1
15
1
1
Order By: Relevance
“…It should be mentioned that thujone may accumulate in some less frequently used and investigated species of the Lamiaceae family, too. For example, higher amounts were detected in Plectranthus species, where a-thujone accumulated up to 28% of the EO (Mota et al 2014) and in Phlomis ferruginea in 5.5% (Formisano et al 2006). Similarly, a-thujone was detected by Kaurinovic et al (2010) in 2.1-3.3% in samples of Marrubium peregrinum, nevertheless even the accumulation rate of total volatiles was very low (0.09-0.14% DW.…”
Section: Occurence Of Thujone In Aromatic Plants Chemotaxonomic Aspectsmentioning
confidence: 94%
“…It should be mentioned that thujone may accumulate in some less frequently used and investigated species of the Lamiaceae family, too. For example, higher amounts were detected in Plectranthus species, where a-thujone accumulated up to 28% of the EO (Mota et al 2014) and in Phlomis ferruginea in 5.5% (Formisano et al 2006). Similarly, a-thujone was detected by Kaurinovic et al (2010) in 2.1-3.3% in samples of Marrubium peregrinum, nevertheless even the accumulation rate of total volatiles was very low (0.09-0.14% DW.…”
Section: Occurence Of Thujone In Aromatic Plants Chemotaxonomic Aspectsmentioning
confidence: 94%
“…The essential oil of Plectranthus barbatus from Taiz region of Yemen has been found to have α-terpinene (2.8%), p -cymene (9.3%), γ-terpinene (20.0%), thymol (48.7%), β-caryophyllene (6.4%) and β-selinene (2.1%) as the major constituents [ 16 ]. The chemical composition of Yemeni Plectranthus barbatus was very different from a Plectranthus barbatus sample from Portugal, which was devoid of thymol [ 93 ]. The Taiz oil sample was subjected to antimicrobial, antifungal, and cytotoxic assays against MCF-7 and MDA-MB-231 cancer cells.…”
Section: Aromatic Medicinal Plants From Yemenmentioning
confidence: 99%
“…The essential oil of P. neochilus displays antischistosomal [ 12 ] and insecticidal [ 15 ] activities. Recently, researchers have applied diffusion in agar disc to assess the antimicrobial activity of the essential oil of a specimen of P. neochilus collected in Portugal against Bacillus cereus , Bacillus subtilis , Staphylococcus aureus , Listeria monocytogenes , Escherichia coli , Pseudomonas aeruginosa , Helicobacter pylori , and Saccharomyces cerevisiae [ 16 ]. The authors reported that the activity of this essential oil against the selected microorganisms was between low and moderate.…”
Section: Introductionmentioning
confidence: 99%